Effect of perceived value, risk, attitude and environmental consciousness on the purchase intention. (26th February 2020) - Souza, Josefer De Lima; Tondolo, Vilmar Antonio Gonçalves; Sarquis, Aléssio Bessa; Longaray, André Andrade; Tondolo, Rosana Da Rosa Portella; Costa, Larissa Martinatto Da
The study analysed the effect of perceived value, risk, attitude and environmental consciousness on the purchase intention of university students for remanufactured computers. This is a cross-sectional quantitative study. Data were collected by questionnaire; 241 students from different institutions of higher education participated. The main analysis techniques used were Pearson correlation analysis and multiple regression modelling. The results showed that there is a strong association between the constructs purchase intention and consumer attitude and a moderate association with perceived value. The results of the regression analysis indicate that the constructs consumer attitude, perceived value and risk predict 66.2% of the intention to purchase remanufactured computers. The study contribute to the literature by analysing several constructs related to the purchase intention of consumers of remanufactured computers and giving a social direction to the study of remanufacturing